Identification of some microbial flora contained in slaughterhouse effluent and likely to be effective in its treatment by biological process - Esther Maurelle Ngouyamnsa Ghenmi; Djonga Weldi Gnowe; Eric Noubissie; Guy Bertrand Noumi; Ali Ahmed (IWA Publishing, 2023)
The specific contributions of the different bacterial flora during the biological treatment of slaughterhouse effluents remain unclear. The objective of this study is to identify the different microbial flora which mainly contribute to the efficiency of the biodegradation of the organic, nitrogenous and phosphate loads contained in the slaughterhouse effluent during its biological treatment. To achieve this, the effluent to be treated was sampled from three slaughterhouses in the city of Ngaoundéré (Cameroon). The various effluents underwent a physicochemical and microbiological characterization. The effluent was subjected to biological treatment. The biodegradation process (biological treatment) took place in two reactors, each operating in batch. One of the two reactors was supplied with oxygen (aeration). The effluent being treated underwent a physicochemical and microbiological characterization for 30 days. The results obtained show organic matter and ammonium contents >1,000 mgO2/L in each of the three effluents. Bacillus cereus (69 × 108 CFU/mL), Pseudomonas aeruginosa (201 × 107 colony forming unit (CFU)/mL) and Yeasts (101 × 106 CFU/mL) globally constitute the majority of microbial groups among the seven microorganisms identified in the effluents of the three slaughterhouses. There is no real oxygenation effect of the medium on the growth of the three microbial flora during the treatment. HIGHLIGHTS The presence of oxygen promotes the rate of elimination of the pollutant load without impacting microbial growth.; The quality of the pollutant favours microbial growth more than the concentration of the pollutant.; The concentration of the pollutant load is influenced by the microbial load during treatment.; The pollutant load varies from one microorganism to another.;